+CIl / +CUl Derivational Affix and the Word undefinedArchaicundefined in Turkey Turkish - Kayasandık, Ahmet (My University, 2020)
Türkçede yeni kelimeler yapmanın yollarından biri yapımekleriyle kelimeler türetmektir. Ancak bunun dilin kurallarınauygun olarak yapılması gerekir. Ek canlı olmalı, benzer örnekleri bulunmalı, kuruluşu tutarlı, yapısı doğru, anlamı açık olmalıdır. Eski kaynaklarda sınırlı örnekleri bulunan +CIl / +CUlekiyle düşkünlük, alışkınlık, benzerlik kavramı taşıyan kelimeler türetilmiştir. Son zamanlarda ekin asıl işlevine getirildiğiisme bağımlılık, yakınlık, isteklilik, sıralama gibi kavramlaryüklenmiş; sayıca az olsa da yine bu ekle bazı araç, gereç adları,bitki adları, oyun adları, terimler ve somut kelimeler yapılmıştır. Eskicil gibi birkaç örnekte ise bu eke, terim türetme ilkelerine pek de uygun olmadığı hâlde nispet eki işlevi yüklenmiştir.Bu çalışmada ekin kelimeye kattığı kavramlar göz önünde bulundurularak bu ekle türetilen bütün kelimeler gruplandırılmışve sözlük anlamları verilmiştir. Ayrıca arkaik yerine kullanılanterimlerden biri olan eskicil sözünün terim yapma yöntemlerineuygun olmadığı belirtilerek bu terim için arkaik veya eski dilögesi ya da eski unsur ifadeleri önerilmiştir.

One of the ways to make new words in Turkish is to derive words with suffixes. However, this must be done in accordance with the rules of the language. The annex must be alive, have similar examples, be consistent in structure, have the right structure, and clear meaning. Words with the concept of indulgence, familiarity and similarity are derived with the suffix + CIl / + CUl, which have limited examples in ancient sources. Recently, concepts such as addiction, closeness, willingness, and sorting were added to the original function of the supplement. Although there are few numbers, some tools, equipment names, plant names, game names, terms and concrete words have been made. In a few examples, such as the word “eskicil”, this suffix has been loaded with a relative suffix function, although it is not very well suited to the term derivation principles. In this study, considering the concepts that the suffix adds to the word, all the words derived with this suffix are grouped and their dictionary meanings are given. In addition, it is stated that the word “eskicil” which is one of the terms used instead of archaic is not suitable for the methods of making terms and archaic or old language or old element expressions are suggested for this term.
Türkiye Türkçesinde +CIl / +CUl eki ve 'eskicil' sözü
Keywords: Dil Ve Dil Bilim